2015
DOI: 10.2298/hemind131115033s
|View full text |Cite
|
Sign up to set email alerts
|

Study on the quality of ground, spring and river waters in south-east Serbia

Abstract: The study deals with mineral characterization of natural waters from South-East Serbia. The contents of aluminium, arsenic, calcium, cadmium, cobalt, chromium, cooper, iron, potassium, magnesium, manganese, sodium, nickel, lead and zinc were analysed in spring, ground and river waters by inductively coupled plasma-atomic emission spectrometry (ICP-AES) technique. The study area was in the Southern Serbia, and included slopes of Rtanj, Ozren, Bukovik, Vrdenik and Cemernik mountains, and the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that there are insufficient amounts of Zn in the soil (Dragović et al 2008 ; Nikolić et al 2016 ), drinking water (Stojanović et al 2015 ) and food (Djinovic-Stojanovic et al 2017 ) in Serbia. To resolve the important question of potential Zn deficiency in the Serbian population, in this study, we investigated different clinical samples including serum, cerebrospinal fluid (CSF), whole blood and Zn-rich tissues, primarily thyroid and brain tissues.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have reported that there are insufficient amounts of Zn in the soil (Dragović et al 2008 ; Nikolić et al 2016 ), drinking water (Stojanović et al 2015 ) and food (Djinovic-Stojanovic et al 2017 ) in Serbia. To resolve the important question of potential Zn deficiency in the Serbian population, in this study, we investigated different clinical samples including serum, cerebrospinal fluid (CSF), whole blood and Zn-rich tissues, primarily thyroid and brain tissues.…”
Section: Introductionmentioning
confidence: 97%
“…or national legislation. Based on the hydrological data and the presence/availability of water resources, Serbia is one of the European countries with an abundance of easily accessible sources of drinking water, which currently satisfy the population needs [4]. The most recent research of the quality of water obtained investigating seven of the biggest rivers in Serbia (Danube, Sava, Drina, Tisa, Velika Morava, Zapadna Morava and Južna Morava) has demonstrated that the River Drina's water mostly complied with the national legislation requirements regarding chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Oc cur rence of met als in sur face wa ters can be due to nat u ral sources (pre cip i tation and geo chem i cal sources, i. e. dis so lu tion of nat urally oc cur ring min er als con tain ing trace el e ments in the soil zone). Anthropogenic sources such as min ing, fu els, smelt ing of ores and im proper dis posal of in dus trial and mu nic i pal wastes, sig nif i cantly con trib ute to el e vated lev els of met als in wa ters [10,11].…”
Section: Introductionmentioning
confidence: 99%